Peningkatan Kemampuan Masyarakat Desa Tirtonirmolo dalam Pengolahan Limbah Peternakan Menjadi Pupuk Organik - Maryudi, Maryudi; Aktawan, Agus (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Indonesia is an agricultural country and many people own livestock. Livestock produces solid manure waste that can be converted into organic fertilizers. Livestock waste has not been treated properly, so community service was conducted to overcome this issue. Community service activities were conducted in the form of training on livestock waste processing into solid organic fertilizer and liquid organic fertilizer for members of The Community Self-Reliance Agency (BKM) "Tirtorahayu" Tirtonirmolo Village, Kapanewon Kasihan, Bantul. The products are useful and have high economic value, so they also have the potential to improve the economy of the residents of Tirtonirmolo Village. Research methodology: Community Service activities in the form of socialization and training on the processing of livestock waste into solid organic fertilizer and liquid organic fertilizer for women and gentlemen from the Community Self-Reliance Agency (BKM) “Tirtorahayu” Kalurahan Tirtonirmolo, Kapanewon Kasihan, Bantul. Result: The implementation of community service activities was in the form of socialization and training on processing livestock waste into solid and liquid organic fertilizers. Livestock waste is converted into solid and liquid fertilizers. Limitations: Activities were conducted during the covid-19 pandemic, so there were limited participants to avoid crowding. There were also limited time and interactions with participants Contributions: The villagers were encouraged to improve their skills in handling livestock waste. They have the opportunity to earn income from the production of solid and liquid organic fertilizers.